2018
DOI: 10.1161/strokeaha.118.020679
|View full text |Cite
|
Sign up to set email alerts
|

Combining Spot Sign and Intracerebral Hemorrhage Score to Estimate Functional Outcome

Abstract: In the PREDICT cohort, a prognostic score adding the computed tomographic angiography-based spot sign to the established ICH score did not improve functional outcome prediction compared with the ICH score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Hematoma volume has been established as the strongest independent predictor of clinical outcome following spontaneous ICH and is, therefore, a critical component of all ICH prognostic scores. [4][5][6][25][26][27][28][29] Additional associations between hematoma volume and hematoma location have been identified. 4,11,12,14,30 Because lobar ICH has been consistently associated with improved neurologic outcomes upon comparison to deep ICH, it has been suggested that the higher initial hematoma volumes in lobar ICH may be offset by the poor prognosis associated with increased likelihood of IVH extension in deep ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma volume has been established as the strongest independent predictor of clinical outcome following spontaneous ICH and is, therefore, a critical component of all ICH prognostic scores. [4][5][6][25][26][27][28][29] Additional associations between hematoma volume and hematoma location have been identified. 4,11,12,14,30 Because lobar ICH has been consistently associated with improved neurologic outcomes upon comparison to deep ICH, it has been suggested that the higher initial hematoma volumes in lobar ICH may be offset by the poor prognosis associated with increased likelihood of IVH extension in deep ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Identify the image symmetry of the bilateral hemispheres Extra-axial lesions Epidural and subdural space [29] Interhemispheric fissure Sylvian fissure Ventricles Lateral ventricles Anterior and posterior horns of lateral ventricles Temporal horns of lateral ventricles Fourth ventricle Specific regions Cerebellopontine angle Sella lesion Vessels Hyperdense MCA sign [15] Hyperdense BA sign [14] Veins: Dense sinus signs of CVT [22] Orbital cavity (Ophthalmic vein enlargement, orbital mass) [17] Intra-axial lesion ACA territory PCA territory MCA territory, basal ganglia and thalamus [24] Borderzone areas [26] MCA-ACA border zone MCA-PCA border zone Temporal lobes Mass effect, mid-line shift, or herniation [25] Brain stem Mid-brain Pons Medulla Cerebellum: symmetry, hyperdensity, hypodensity of the cerebellar hemispheres.5. Identify abnormal densities on brain CT [27, 28] Identify hyper-density lesions Hematoma density Physiological calcification density Identify low density lesions Very low density (CSF and old lesions) Low density (edematous lesion and recent infarcts) Identify heterogeneous density lesions Hematoma with blended sign [18], whirl sign [19], spot sign [21], or black hole sign [20] Low density mixed with hyper-density (hemorrhagic infarct) Identify mass-like lesions ABBBC (Air-Blood-Bone-Brain-CSF) mnemonic [30] ACA anterior cerebral artery, CSF cerebrospinal fluid, CT computerized tomography, CVT cerebral venous thrombosis, ID identification, MCA middle cerebral artery, PCA posterior cerebral artery…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the spot sign helps identify ICH survivors who might require surgical intervention and longer in-patient treatment course. Combining the CTA spot sign with other prognostic tools is also an option [15], but more research on this topic is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have revealed that the spot sign is associated with higher mortality, hematoma expansion, and worse functional outcomes in patients with ICH, indicating the predictive value of the spot sign. However, these studies determined the endpoint of functional outcome solely based on the mRS score and the study population included patients who died (mRS = 6) during the acute disease phase, which might obscure the predictability of the spot sign in ICH survivors [9,15]. In the present study, we determined functional outcomes based on both BI and mRS scores, which are better in characterizing ADLs.…”
Section: Spot Sign and Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation